Lymphocyte-dependent antibody-mediated cytotoxicity in Hashimoto thyroiditis - Calder, E A; Penhale, W J; McLeman, D; Barnes, E W; Irvine, W J (Clinical and experimental immunology, 1973)
In the presence of normal human lymphocytes, decomplemented sera from twentynine out of thirty-nine patients with Hashimoto thyroiditis caused significant lysis of thyroglobulin-coated chicken red blood cells, as estimated by the release of 51Cr; the mean% specific 51Cr release being 14·1 ± 1·9 (SEM). Serum from twenty-one control subjects studied concurrently caused no significant lysis of thyroglobulin-coated chicken red blood cells; the mean% specific 51Cr release being −1·6±0·7 (SEM). The degree of cytotoxicity correlated with the titre of thyroglobulin antibodies in the serum, determined by tanned red cell haemagglutination. The active component in the Hashimoto serum was localized in the 19S fraction, was unaffected by pre-absorption with anti-human IgM serum, but was neutralized by pre-absorption with anti-human IgG serum. These findings suggest that the cytotoxic activity of serum from patients with Hashimoto thyroiditis is due to the presence of thyroglobulin antibody of the IgG class in the form of complexes, either alone or with antigen. It is postulated that non-specific lymphocytes may play an important role in the pathogenesis of Hashimoto thyroiditis, being activated by the presence in the gland of thyroglobulin antibody, either alone or in the form of complexes attached to thyroid cells.